Uji Aktivitas Antihiperglikemi Secara Invitro Terhadap Fraksi Ekstrak Metanol Bawang Merah Dan Bawang Bombay - Erlindha Gangga; Erwin Suyanto (Proceeding of Mulawarman Pharmaceuticals Conferences, 2016)
The number of people with diabetes mellitus in Indonesia recorded by the World Health Organization in 2030 expected will reach 21.3 million people. Danger of side effects of synthetic drugs makes people seek alternative medicine solutions. Alternative medicine in question is natural medicine. Shallots(Allium cepa var.ascalonicum (L.) Back),onions(Allium cepa L.) and garlic comes from family Liliaceae, which contains quercetin. Quercetin is found in garlic bulbs can inhibit the action of the enzyme ?-glucosidase in the small intestine of mice . With the inhibition of the enzyme ?-glucosidase cleavage and absorption of carbohydrates will be disrupted. Quercetin has multiple hydroxyl groups in its structure, so that the solubility of quercetin in polar solvents are better such as water, methanol and ethanol. In this study, the methanol extract of shallots and onions partitioned into n-hexane phase, ethyl acetate phase, n-butanol phase and the aqueous phaseonce that is done ?-glucosidase inhibition assay in vitro. The test showed that the methanol extract of onion has IC50 of 13.49 ppm , methanol extracts of onion has IC50 of 15.50 ppm. The test results showed methanol extract of onion, methanol extracts of onion has inhibition of ?-glukosidase activity which indicates effect.